Examples with solutions for Powers of a Fraction: Variable in the base of the power

Exercise #1

Insert the corresponding expression:

(xy)8= \left(\frac{x}{y}\right)^8=

Video Solution

Step-by-Step Solution

To solve this problem, we will apply the power of a fraction rule:

Step 1: Recognize that we are asked to simplify (xy)8\left(\frac{x}{y}\right)^8.

Step 2: Apply the power of a fraction rule, which states:

  • (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}

Step 3: Use this formula to obtain:

(xy)8=x8y8\left(\frac{x}{y}\right)^8 = \frac{x^8}{y^8}

Therefore, the simplified expression of (xy)8\left(\frac{x}{y}\right)^8 is x8y8\frac{x^8}{y^8}.

The correct choice from the given options is:

x8y8 \frac{x^8}{y^8}

Answer

x8y8 \frac{x^8}{y^8}

Exercise #2

Insert the corresponding expression:

(ab)9= \left(\frac{a}{b}\right)^9=

Video Solution

Step-by-Step Solution

The problem asks us to express (ab)9\left(\frac{a}{b}\right)^9 using exponent rules. We will use the rule for the power of a fraction, which states:

(ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}

Applying this rule, we get:

(ab)9=a9b9\left(\frac{a}{b}\right)^9 = \frac{a^9}{b^9}

This method ensures that the exponent 99 is applied to both the numerator and the denominator of the fraction.

Therefore, the solution to the problem is a9b9\frac{a^9}{b^9}.

Answer

a9b9 \frac{a^9}{b^9}

Exercise #3

Insert the corresponding expression:

(a3)2= \left(\frac{a}{3}\right)^2=

Video Solution

Step-by-Step Solution

We need to rewrite the expression (a3)2\left(\frac{a}{3}\right)^2 using the rule of exponents for fractions. This rule states that if you have a fraction (mn)\left(\frac{m}{n}\right) and you raise it to a power kk, it is equivalent to raising both the numerator and the denominator to the power kk. Therefore, we have:

(a3)2=a232 \left(\frac{a}{3}\right)^2 = \frac{a^2}{3^2}

Here, a2a^2 is the numerator and 323^2 is the denominator. The expression simplifies to:

a29 \frac{a^2}{9}

Based on the provided choices, the correct answer is:

Choice 1: a232 \frac{a^2}{3^2}

Therefore, the solution to the given problem is a232 \frac{a^2}{3^2} .

Answer

a232 \frac{a^2}{3^2}

Exercise #4

Insert the corresponding expression:

(b5)4= \left(\frac{b}{5}\right)^4=

Video Solution

Step-by-Step Solution

To solve this problem, we'll apply the exponent rule for fractions:

  • Step 1: Identify the fraction b5\frac{b}{5} and the power 44.
  • Step 2: Apply the exponent to both the numerator and the denominator, as per the formula.
  • Step 3: Use the rule (b5)4=b454 \left(\frac{b}{5}\right)^4 = \frac{b^4}{5^4} .

Now, let's work through the application:
Step 1: We have the base fraction b5\frac{b}{5} and exponent 44.
Step 2: According to the exponent rule, (ab)n=anbn \left(\frac{a}{b}\right)^n = \frac{a^n}{b^n} , apply the exponent 44 to both bb and 55.
Step 3: This results in the expression b454\frac{b^4}{5^4}.

Therefore, the expression (b5)4 \left(\frac{b}{5}\right)^4 simplifies to b454 \frac{b^4}{5^4} .

Answer

b454 \frac{b^4}{5^4}

Exercise #5

Insert the corresponding expression:

(6x)3= \left(\frac{6}{x}\right)^3=

Video Solution

Step-by-Step Solution

To solve this problem, we will rewrite the expression (6x)3\left(\frac{6}{x}\right)^3 using the power of a fraction rule. The steps are as follows:

  • Identify the fraction's numerator 66 and denominator xx.

  • According to the power of a fraction rule, apply the power 3 to both the numerator and the denominator:

  • (6x)3=63x3\left(\frac{6}{x}\right)^3 = \frac{6^3}{x^3}.

Therefore, the expression is correctly written as 63x3 \frac{6^3}{x^3} .

Comparing with the provided answer choices, the correct choice is choice 22:

63x3 \frac{6^3}{x^3}

Answer

63x3 \frac{6^3}{x^3}

Exercise #6

Insert the corresponding expression:

(5y)7= \left(\frac{5}{y}\right)^7=

Video Solution

Step-by-Step Solution

To solve this problem and transform the expression (5y)7\left(\frac{5}{y}\right)^7, we need to utilize the exponent rule for powers of fractions:

  • Step 1: Recognize that the expression (5y)7\left(\frac{5}{y}\right)^7 involves both the numerator 5 and the denominator yy.
  • Step 2: According to the exponent rule (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}, we can apply the exponent of 7 to both the numerator and the denominator.
  • Step 3: Applying this rule gives us 57y7\frac{5^7}{y^7}. This step distributes the power to each component of the fraction, preserving the structure of the expression.

Thus, the simplified form of the expression (5y)7\left(\frac{5}{y}\right)^7 is 57y7\frac{5^7}{y^7}.

This matches choice 3 from the provided options.

Answer

57y7 \frac{5^7}{y^7}

Exercise #7

Insert the corresponding expression:

(4a×b)2= \left(\frac{4}{a\times b}\right)^2=

Video Solution

Step-by-Step Solution

To solve the problem, let's apply exponent rules to the given expression:

  • Step 1: Identify the fraction's components. The numerator is 44 and the denominator is a×ba \times b.
  • Step 2: Apply the exponent rule for fractions, (mn)p=mpnp\left(\frac{m}{n}\right)^p = \frac{m^p}{n^p}. In this case, m=4m = 4, n=a×bn = a \times b, and p=2p = 2.

Now, we apply the exponent:

(4a×b)2=42(a×b)2\left(\frac{4}{a \times b}\right)^2 = \frac{4^2}{(a \times b)^2}.

This results in:

16a2×b2\frac{16}{a^2 \times b^2}.

However, the expression 42(a×b)2\frac{4^2}{(a \times b)^2} matches choice 2 from the provided options, hence:

The correct answer to the problem in its intended form is 42(a×b)2 \frac{4^2}{\left(a\times b\right)^2} .

Answer

42(a×b)2 \frac{4^2}{\left(a\times b\right)^2}

Exercise #8

Insert the corresponding expression:

(5x×y)5= \left(\frac{5}{x\times y}\right)^5=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Recognize the expression as an example of a power of a fraction.
  • Step 2: Apply the power of a fraction rule to the expression.
  • Step 3: Compare the resulting expression with the answer choices.

Now, let's work through each step:
Step 1: The given expression is (5x×y)5\left(\frac{5}{x \times y}\right)^5.
Step 2: Apply the power of a fraction rule: (ab)n=anbn\left(\frac{a}{b}\right)^n = \frac{a^n}{b^n}. This gives us:

(5x×y)5=55(x×y)5 \left(\frac{5}{x \times y}\right)^5 = \frac{5^5}{(x \times y)^5}

Step 3: Compare with answer choices:

  • Choice 1: 55(x×y)5\frac{5^5}{(x \times y)^5} matches our expression exactly.
  • Choice 2: 55x5×y5\frac{5^5}{x^5 \times y^5} results from distributing the exponent across the product in the denominator, which is another valid interpretation.
  • Choice 3: Indicates both expressions in choices 1 and 2 (a'+b') are correct interpretations of the expanded form.
  • Choice 4: 55x×y5\frac{5^5}{x \times y^5} is incorrect as it improperly applies the exponent only to yy.

Therefore, the solution to the problem, which captures both possible expressions, is a'+b' are correct.

Answer

a'+b' are correct

Exercise #9

Insert the corresponding expression:

(a×x7)6= \left(\frac{a\times x}{7}\right)^6=

Video Solution

Step-by-Step Solution

To solve this problem, we'll utilize the properties of exponents to simplify the expression (a×x7)6 \left(\frac{a \times x}{7}\right)^6 .

Let's proceed with the steps:

  • Step 1: Utilize the exponent rule for fractions: (mn)p=mpnp \left( \frac{m}{n} \right)^p = \frac{m^p}{n^p} . This allows us to express the given expression as:

(a×x7)6=(a×x)676 \left(\frac{a \times x}{7}\right)^6 = \frac{(a \times x)^6}{7^6}

  • Step 2: Apply the exponent rule to the multinomial in the numerator: (a×x)6=a6×x6 (a \times x)^6 = a^6 \times x^6 .

Thus, we have:

(a×x)676=a6×x676 \frac{(a \times x)^6}{7^6} = \frac{a^6 \times x^6}{7^6}

Conclusion: The correct expression is a6×x676\frac{a^6 \times x^6}{7^6} , which corresponds to choice 4.

Answer

a6×x676 \frac{a^6\times x^6}{7^6}

Exercise #10

Insert the corresponding expression:

(a×bx×y)2= \left(\frac{a\times b}{x\times y}\right)^2=

Video Solution

Step-by-Step Solution

Let's work through the solution step-by-step:

Step 1: Identify the expression
We are given the expression (a×bx×y)2\left(\frac{a \times b}{x \times y}\right)^2.

Step 2: Apply the power of a fraction rule
Using the rule (mn)p=mpnp\left(\frac{m}{n}\right)^p = \frac{m^p}{n^p}, we can rewrite the expression as:

(a×b)2(x×y)2\frac{(a \times b)^2}{(x \times y)^2}.

Which matches option 1.

Step 3: Apply the distributive property of exponents over multiplication
Using the rule (m×n)p=mp×np(m \times n)^p = m^p \times n^p, each part of the expression is expanded:

(a×b)2=a2×b2(a \times b)^2 = a^2 \times b^2 and (x×y)2=x2×y2(x \times y)^2 = x^2 \times y^2.

Thus, the expression becomes:

a2×b2x2×y2\frac{a^2 \times b^2}{x^2 \times y^2}.

Step 4: Identify the correct choice
Looking at the provided options, choice 3 is:

a2×b2x2×y2 \frac{a^2 \times b^2}{x^2 \times y^2} and option 1 is(a×b)2(x×y)2\frac{(a \times b)^2}{(x \times y)^2}

Both expression matches our derived solution, confirming that the correct answer is choice 4, A+C are correct.

Answer

A'+C' are correct

Exercise #11

Insert the corresponding expression:

(x×ab×y)4= \left(\frac{x\times a}{b\times y}\right)^4=

Video Solution

Step-by-Step Solution

To solve this problem, we'll utilize the rules of exponents, particularly the rule for raising fractions to a power.

  • Step 1: Recognize that the expression (x×ab×y)4\left(\frac{x \times a}{b \times y}\right)^4 has a fraction raised to a power.
  • Step 2: Apply the rule (mn)p=mpnp\left(\frac{m}{n}\right)^p = \frac{m^p}{n^p} to distribute the exponent of 4 to both the numerator and the denominator.
  • Step 3: This means (x×ab×y)4=(x×a)4(b×y)4 \left(\frac{x \times a}{b \times y}\right)^4 = \frac{(x \times a)^4}{(b \times y)^4} .
  • Step 4: Use the power of a product rule: (m×n)p=mp×np(m \times n)^p = m^p \times n^p, which allows us to write (x×a)4(x \times a)^4 as x4×a4x^4 \times a^4 and (b×y)4(b \times y)^4 as b4×y4b^4 \times y^4.
  • Step 5: Substitute these results back into the expression to get x4×a4b4×y4\frac{x^4 \times a^4}{b^4 \times y^4}.

Therefore, the simplified expression is x4×a4(b×y)4 \frac{x^4 \times a^4}{\left(b \times y\right)^4} .

Answer

x4×a4(b×y)4 \frac{x^4\times a^4}{\left(b\times y\right)^4}

Exercise #12

Insert the corresponding expression:

(a×b2×x)3= \left(\frac{a\times b}{2\times x}\right)^3=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Express the given expression (a×b2×x)3\left(\frac{a \times b}{2 \times x}\right)^3 using exponent rules for fractions.
  • Step 2: Apply the cube power to both the numerator and the denominator separately.
  • Step 3: Simplify the expression and compare it to the provided choices.

Now, let's work through each step:

Step 1: We have the expression (a×b2×x)3\left(\frac{a \times b}{2 \times x}\right)^3. According to the power of a fraction rule, (mn)p=mpnp\left(\frac{m}{n}\right)^p = \frac{m^p}{n^p}, we can raise the numerator and denominator to the power of 3 separately.

Step 2: Apply the cube power:

  • Numerator: (a×b)3=a3×b3(a \times b)^3 = a^3 \times b^3
  • Denominator: (2×x)3=23×x3=8×x3(2 \times x)^3 = 2^3 \times x^3 = 8 \times x^3

Step 3: Combine these results:

The expression simplifies to a3×b38×x3\frac{a^3 \times b^3}{8 \times x^3}.

Comparing it to the given choices, we find that this matches Choice 1: a3×b38×x3\frac{a^3 \times b^3}{8 \times x^3}.

Therefore, the solution to the problem is a3×b38×x3\frac{a^3 \times b^3}{8 \times x^3}.

Answer

a3×b38×x3 \frac{a^3\times b^3}{8\times x^3}

Exercise #13

Insert the corresponding expression:

(a×32×x)3= \left(\frac{a\times3}{2\times x}\right)^3=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given expression and its structure.
  • Step 2: Apply the rule for powers of a fraction, (pq)n\left(\frac{p}{q}\right)^n.
  • Step 3: Calculate powers of individual components within the fraction.
  • Step 4: Simplify the resulting expression.

Now, let's work through each step:

Step 1: Our given expression is (a×32×x)3\left(\frac{a \times 3}{2 \times x}\right)^3.

Step 2: Apply the power to the entire fraction using (pq)n=pnqn\left(\frac{p}{q}\right)^n = \frac{p^n}{q^n}, we get:
(a×32×x)3=(a×3)3(2×x)3 \left(\frac{a \times 3}{2 \times x}\right)^3 = \frac{(a \times 3)^3}{(2 \times x)^3} .

Step 3: Simplify the numerator and the denominator separately:
Numerator: (a×3)3=a3×33=a3×27(a \times 3)^3 = a^3 \times 3^3 = a^3 \times 27.
Denominator: (2×x)3=23×x3=8×x3(2 \times x)^3 = 2^3 \times x^3 = 8 \times x^3.

Step 4: Combine the simplified components to form the final expression:
The expression is a3×278×x3\frac{a^3 \times 27}{8 \times x^3}.

Therefore, the solution to the problem is a3×278×x3 \frac{a^3 \times 27}{8 \times x^3} , which corresponds to choice 2.

Answer

a3×278×x3 \frac{a^3\times27}{8\times x^3}

Exercise #14

Insert the corresponding expression:

(6x×y)2= \left(\frac{6}{x\times y}\right)^2=

Video Solution

Step-by-Step Solution

To solve this problem, we'll apply the rule for powers of a fraction:

  • Step 1: Identify the fraction. The fraction given is 6x×y\frac{6}{x \times y}.
  • Step 2: Apply the power to both the numerator and the denominator. This means squaring both 6 and x×yx \times y.
  • Step 3: Calculate the square of the numerator and the denominator:
    • The square of the numerator: 62=366^2 = 36.
    • The square of the denominator: (x×y)2=x2×y2(x \times y)^2 = x^2 \times y^2.
  • Step 4: Combine the results: (6x×y)2=62(x×y)2=36x2×y2\left(\frac{6}{x \times y}\right)^2 = \frac{6^2}{(x \times y)^2} = \frac{36}{x^2 \times y^2}.

Thus, the expression (6x×y)2\left(\frac{6}{x \times y}\right)^2 simplifies to 36(x×y)2\frac{36}{(x \times y)^2}.

Therefore, the correct answer is clearly the expression 36(x×y)2\frac{36}{(x \times y)^2}, which matches choice 4.

Answer

36(x×y)2 \frac{36}{\left(x\times y\right)^2}

Exercise #15

Insert the corresponding expression:

(2×a3)2= \left(\frac{2\times a}{3}\right)^2=

Video Solution

Step-by-Step Solution

The task is to simplify (2×a3)2\left(\frac{2\times a}{3}\right)^2.

First, applying the exponent rule for fractions, (bc)n=bncn\left(\frac{b}{c}\right)^n = \frac{b^n}{c^n}, we have:

  • (2×a3)2=(2×a)232\left(\frac{2\times a}{3}\right)^2 = \frac{(2 \times a)^2}{3^2} - which represents performing the exponentiation separately on the numerator and denominator.

Now, simplify each part:

  • The numerator: (2×a)2=22×a2=4×a2(2 \times a)^2 = 2^2 \times a^2 = 4 \times a^2.
  • The denominator: 32=93^2 = 9.

Thus, the expression simplifies to 4×a29\frac{4 \times a^2}{9}.

We ensure the valid transformations based on the choices provided:

  • Choice 1: 4×a29\frac{4\times a^2}{9}, which matches what we calculated.
  • Choice 2: 22×a232\frac{2^2\times a^2}{3^2}, which is an equivalent form before final multiplication.
  • Choice 3: (2×a)232\frac{\left(2\times a\right)^2}{3^2}, presenting the step before breaking down the (2a)2 (2a)^2 .
  • Choice 4: "All answers are correct", recognizing all transformations as valid.

Therefore, each choice represents correct steps or forms towards the simplified expression.

The correct answer is: All answers are correct.

Answer

All answers are correct

Exercise #16

Insert the corresponding expression:

38×a8x8×58= \frac{3^8\times a^8}{x^8\times5^8}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll rewrite the given fraction 38×a8x8×58\frac{3^8 \times a^8}{x^8 \times 5^8} using the rules of powers and exponents.

  • Step 1: Recognize the overall structure of the fraction is m8×n8p8×q8\frac{m^8 \times n^8}{p^8 \times q^8}.
  • Step 2: Apply the rule of exponents to express it as a single power of the entire fraction: (m×np×q)8\left(\frac{m \times n}{p \times q}\right)^8.
  • Step 3: Substitute the values: (3×ax×5)8\left(\frac{3 \times a}{x \times 5}\right)^8 simplifies the expression effectively, given that all components are non-zero.

Thus, by applying the exponent rule directly to the entire fraction, we simplify to (3×ax×5)8\left(\frac{3 \times a}{x \times 5}\right)^8.

Answer

(3×ax×5)8 \left(\frac{3\times a}{x\times5}\right)^8

Exercise #17

Insert the corresponding expression:

a5×x575×b5= \frac{a^5\times x^5}{7^5\times b^5}=

Video Solution

Step-by-Step Solution

To solve this problem, our goal is to express the given quotient of powers in a simplified form using exponent laws.

  • Step 1: Understand the original expression. We have a5×x575×b5\frac{a^5 \times x^5}{7^5 \times b^5}.
  • Step 2: Recognize the structure. Notice that both the numerator and denominator are raised to the fifth power.
  • Step 3: Apply the property of exponents for quotients and products, which states that (mn)k=mknk\left(\frac{m}{n}\right)^k = \frac{m^k}{n^k} and (mn)k=mknk(m \cdot n)^k = m^k \cdot n^k.
  • Step 4: Rewrite the expression as a single fraction raised to the power of 5. Since each term in the numerator and denominator is raised to the fifth power separately, we combine them under a single power:
    • Numerator: a5×x5=(a×x)5a^5 \times x^5 = (a \times x)^5
    • Denominator: 75×b5=(7×b)57^5 \times b^5 = (7 \times b)^5
    • Therefore, a5×x575×b5=(a×x7×b)5\frac{a^5 \times x^5}{7^5 \times b^5} = \left(\frac{a \times x}{7 \times b}\right)^5.

Thus, the expression can be written as: (a×x7×b)5\left(\frac{a \times x}{7 \times b}\right)^5.

Now, comparing this with the answer choices provided:

  • Choice 1: (a×x)57×b5\frac{(a \times x)^5}{7 \times b^5} - does not match, as it retains the separate powers incorrectly.
  • Choice 2: (a×x7×b)5\left(\frac{a \times x}{7 \times b}\right)^5 - matches perfectly as derived.
  • Choice 3: a×x5(7×b)5\frac{a \times x^5}{(7 \times b)^5} - incorrect form compared to derived structure.
  • Choice 4: 7×(a×xb)57 \times \left(\frac{a \times x}{b}\right)^5 - unrelated format, doesn't match.

The correct choice is therefore Choice 2. This matches our derived expression using the laws of exponents correctly.

Answer

(a×x7×b)5 \left(\frac{a\times x}{7\times b}\right)^5

Exercise #18

Insert the corresponding expression:

x4a4= \frac{x^4}{a^4}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given information: We have the expression x4a4\frac{x^4}{a^4}.
  • Step 2: Apply the appropriate exponent rule: Use the rule xmym=(xy)m\frac{x^m}{y^m} = \left(\frac{x}{y}\right)^m.
  • Step 3: Simplify the expression using the rule: Substitute mm with 4, xx with xx, and yy with aa.

Now, let's work through each step:
Step 1: The expression is x4a4\frac{x^4}{a^4}.
Step 2: We use the rule xmym=(xy)m\frac{x^m}{y^m} = \left(\frac{x}{y}\right)^m, which states that a fraction where the numerator and denominator are raised to the same power can be expressed as a power of a single fraction.
Step 3: Plugging in the values, we have x4a4=(xa)4\frac{x^4}{a^4} = \left(\frac{x}{a}\right)^4.

Therefore, the solution to the problem is (xa)4 \left(\frac{x}{a}\right)^4 , which corresponds to choice 1.

Answer

(xa)4 \left(\frac{x}{a}\right)^4

Exercise #19

Insert the corresponding expression:

a333×53= \frac{a^3}{3^3\times5^3}=

Video Solution

Step-by-Step Solution

To solve this problem, we need to simplify and express the equation a333×53 \frac{a^3}{3^3 \times 5^3} using exponent rules.

The denominator 33×53 3^3 \times 5^3 can be simplified using the property of exponents: (ab)n=an×bn(ab)^n = a^n \times b^n. This means that:

33×53=(3×5)3 3^3\times5^3=(3\times5)^3 .

Therefore, the expression can be rewritten as:

a3(3×5)3 \frac{a^3}{(3\times5)^3 } which is actually the same as (a3×5)3 \left(\frac{a}{3\times5}\right)^3 , using the identity anbn=(ab)n\frac{a^n}{b^n} = \left(\frac{a}{b}\right)^n.

Thus, the expression can also be written as:

(a3×5)3 \left(\frac{a}{3 \times 5}\right)^3 .

Looking at the provided choices, this expression corresponds to choice marked as (a3×5)3\left(\frac{a}{3 \times 5}\right)^3.

Therefore, the expression matches both rewritten forms:

The correct answer is a'+b' are correct

Answer

a'+b' are correct

Exercise #20

Insert the corresponding expression:

46a6×x6= \frac{4^6}{a^6\times x^6}=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Recognize the given expression 46a6×x6\frac{4^6}{a^6 \times x^6} is a power over a product raised to that power.
  • Step 2: Apply the power of a quotient rule to rewrite the expression.

Now, let's work through each step:
Step 1: The given expression is 46a6×x6\frac{4^6}{a^6 \times x^6}. This can be seen as having common exponents across the numerator and the denominator.
Step 2: Using the power of a quotient rule, which allows us to express the initial expression as (4a×x)6\left(\frac{4}{a \times x}\right)^6. This step involves recognizing that you can treat the entire a×xa \times x as a single base for the denominator.

Hence, the simplified form of the given expression is (4a×x)6\left(\frac{4}{a \times x}\right)^6.

Therefore, the solution to the problem is (4a×x)6 \left(\frac{4}{a \times x}\right)^6 .

Answer

(4a×x)6 \left(\frac{4}{a\times x}\right)^6